The Wealth Discretion Punishment from the Perspective of Islamic Jurisprudence | التعزير بالمال في نظرة الفقه الإسلامي (دراسة تحليلية) - Imam Sujoko (Fakultas Dirasat Islamiyah, Univitas Islam Negeri (UIN) Syarif Hidayatullah Jakarta, 2009)
The objective of the research is to explore meaning of ta’zir bi al-mal, reasoningsof ta’zir, issues concerning branches, types, nature, the principles of ta’zir bi almaland cases related to the ta’zir bi al-mal. The research is undertaken byutilizing the methodology of literature review. After examining both classicaland modern literatures, the writer finds that ta’zir is essentially speculativeoutcome of Muslim jurist that were made based on the Qur’an and Sunah. Sinceit is ijtihad, it is subject to change and non absolute. The study believes thateven though ta’zir is considered speculative, it has its own regulations andobjectives. The research also discusses the significance of the ta’zir bi al-mal(wealth discretion punishment) in order to minimize disobedience ortransgression. The same topic has been written by other researcher, such as;book, article, hand out, and other kind of research. So this research is written inorder to equip, empower and mention some items that have not ben mentionedin other researches.